Analysis of spatial harvest constraints on ecological (wildlife habitat) versus economic (timber harvest) objectives - Kaufmann, Cynthia Kathleen (2000)
The effects of alternative forest management scenarios and spatial constraints were modeled. Specific study area: Nakina North Forest (allocated to Buchanan Forest Products Ltd.) On a northwestern Ontario forest management unit, the effects of alternative forest management scenarios and spatial constraints on both the supply of suitable wildlife habitat and the ability to achieve non-spatially defined timber harvest volume objectives were modeled. The results include a decision surface model that identifies thresholds in the ecological (wildlife habitat) and economic (timber harvest) response variables, and allows managers to determine the “spatial domain” where both ecological and economic objectives converge. Such a model may be a useful approach for initial policy screening in an adaptive management cycle. The Ontario Ministry of Natural Resources’ (OMNR) Strategic Forest Management Model (SFMM), a linear programming optimization model, and Remsoft’s Stanley, a spatial harvest allocation program, were used to explore alternate forest management scenarios. Timber supply and habitat supply for both interior and ecotone wildlife species were examined after five 10-year terms of harvest using various spatial constraints (cut block size, proximity, and green up delay). Habitat Analyst and Patch Analyst, models developed by Dr. R. Rempel at the Center for Northern Forest Ecosystem Research, were used to evaluate habitat supply in both non-spatial and spatial analyses. Consistent with other studies, a green-up constraint had an adverse effect on the amount of available harvest area that could be allocated and blocked spatially. Forest management scenarios using a caribou stratification process of restricting harvest in large (>10,000 ha) blocks had an adverse effect on the amount of available harvest area that could be allocated and blocked spatially. A case study using the application of the caribou stratification constraint and a green up delay of one 10 — year term found the convergence of both economic and ecological objectives when maximum block size was between 200 and 1000 hectares and proximity was between 400 and 1000 meters. This combination of variables also produces a block size distribution approaching the natural disturbance pattern for the area. The study also found that while the use of the caribou stratification constraint improved habitat availability for caribou, it also improved habitat availability for moose and may undermine efforts to conserve caribou.